2017
DOI: 10.1002/jbm.b.33959
|View full text |Cite
|
Sign up to set email alerts
|

In vivo comparison of jellyfish and bovine collagen sponges as prototype medical devices

Abstract: Jellyfish have emerged as a source of next generation collagen that is an attractive alternative to existing sources, such as bovine and porcine, due to a plentiful supply and providing a safer source through lack of bovine spongiform encephalopathy (BSE) transmission risk and potential viral vectors, both of which could be transmitted to humans. Here we compare collagen implantable sponges derived for the first time from the Rhizostoma pulmo jellyfish. A further novelty for the research was that there was a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 39 publications
1
49
0
Order By: Relevance
“…An in vivo comparative study of jellyfish and bovine sponges as prototype medical devices reported that jellyfish collagen is able to stimulate both transcription and translation, thus enhancing immunoglobulin and cytokine production [50]. Results confirmed an immunological response of jellyfish collagen sponges, comparable to that stimulated by bovine collagen and gelatin [50].…”
Section: Jellyfishmentioning
confidence: 88%
See 1 more Smart Citation
“…An in vivo comparative study of jellyfish and bovine sponges as prototype medical devices reported that jellyfish collagen is able to stimulate both transcription and translation, thus enhancing immunoglobulin and cytokine production [50]. Results confirmed an immunological response of jellyfish collagen sponges, comparable to that stimulated by bovine collagen and gelatin [50].…”
Section: Jellyfishmentioning
confidence: 88%
“…Scaffolds for tissue engineering made of collagen extracted from the scytphomedusa Rhizostoma pulmo were successfully implanted into a mouse model and showed optimal adsorption and biocompatibility properties [50]. These findings suggest that collagen derived from scyphomedusae may become a suitable replacement for bovine-derived collagen.…”
Section: Introductionmentioning
confidence: 85%
“…Through the whole experiment, PLGA/coll scaffolds showed increased neutrophil and macrophage infiltration and intensive inflammatory response. This observation was particularly surprising for us, as in general collagen is regarded as biocompatible and low-immunogenic material [ 37 ]. This evidenced that xenograft proteins (in our case collagen obtained from bovine tendons) evoked more pronounced immunological response in rabbits in comparison to synthetic PLGA or biomimetic HAp.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the interspecies difference, collagen is a material of natural origin, thus its properties may vary depending on production batch, purification procedure, or storage conditions [ 41 , 42 , 43 ]. Several concerns over the use of collagen of bovine origin have already been raised, mainly connected to possible transmission of bovine spongiform encephalopathy (BSE) or viruses [ 37 , 44 ]. Thus, novel sources of collagen are being developed, including fish skin, jelly fish, plants, or synthetic KOD (a synthetic analogue of collagen composed of 36 amino acids organized into triple-helixes) [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these sources have problems with Bovine Spongiform Encephalopathy (BSE), other Transmittable Spongiform Encephalopathies (TSEs) and potential viral vectors that could be transmissible to humans [83,84]. More recently, jellyfish have emerged as a source of collagen that is an attractive alternative to existing sources due to a plentiful supply Williams [85] and a safer source through lack of BSE risk and potential viral vectors [86] while exhibiting good performance in vivo when compared to bovine sources [87].…”
Section: Collagenmentioning
confidence: 99%